2016
DOI: 10.5888/pcd13.160193
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Perceptions of Barriers to Diabetic Retinopathy Screening Among Patients and Care Providers, Los Angeles, California, 2014–2015

Abstract: IntroductionDespite availability of screening for diabetic retinopathy, testing is underused by many low-income and racial/ethnic minority patients with diabetes. We examined perceived barriers to diabetic retinopathy screening among low-income patients and their health care providers and provider staffers.MethodsWe collected survey data from 101 patients with diabetes and 44 providers and staffers at a safety-net clinic where annual diabetic retinopathy screening rates were low. Barriers specified in the surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 26 publications
2
42
0
Order By: Relevance
“…28, 29 Some parallels can be drawn to universal diabetic retinopathy screening which only occurs in 49 to 56% of patients, with rates lower among those with lower income and racial and ethnic minorities as well as patients who poorly understood the rationale for screening. 30, 31 Further research to identify and overcome barriers to OSA screening will be necessary to implement more widespread testing.…”
Section: Discussionmentioning
confidence: 99%
“…28, 29 Some parallels can be drawn to universal diabetic retinopathy screening which only occurs in 49 to 56% of patients, with rates lower among those with lower income and racial and ethnic minorities as well as patients who poorly understood the rationale for screening. 30, 31 Further research to identify and overcome barriers to OSA screening will be necessary to implement more widespread testing.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, screening for DR should be done promptly after diagnosis and at regular risk-based intervals thereafter. Numerous factors are known to affect attendance at DR screening [87][88][89][90][91]. In an established mobile retinal screening service in Scotland, poor attendance at screening was not linked to gender or to distance from the event, but was associated with younger age, longer duration of diabetes, smoking, social deprivation, and poor HbA1c and blood pressure control; the highest proportion of non-attenders were in urban areas [92].…”
Section: Barriers To Screeningmentioning
confidence: 99%
“…In a US study of low-income patients and their healthcare providers and staffers, investigators found a striking lack of agreement in perceived barriers to screening [90]. Providers and staffers felt that transportation, language issues, cultural beliefs or myths, denial and fear were key barriers to DR screening, whereas patients indicated that financial burden and depression were the most common barriers [90]. Judah et al [94] evaluated the effectiveness of financially incentivizing screening among patients in the NHS Diabetic Eye Screening Programme who had not attended an appointment for at least 2 years.…”
Section: Barriers To Screeningmentioning
confidence: 99%
“…26 More recent community based studies also report poor rates of screening and monitoring, 27 especially in low income areas and in ethnic minorities, 28 particularly if patients do not understand the need despite availability of services. 29 Effective screening and follow-up are needed to detect retinal changes quickly and accurately, and this should be coupled with education for patients that highlights the need for screening.…”
Section: Pathophysiology and Risk Factors For Dmc In Type 2 Diabetesmentioning
confidence: 99%
“…Overweight Diabetics With Surgery or Best Medicine (PROMISE) is a multicenter RCT that aims to recruit 100 patients with type 2 diabetes, increased weight (body mass index [28][29][30][31][32][33][34][35] and impaired renal function (estimated GFR 30-60 mL/min/1.73 m 2 and albuminuria). 149 All patients will receive optimal medical treatment, and 50 will be randomly assigned to gastric bypass surgery (this would be outside current standard body mass index criteria for surgery).…”
Section: The Upcoming Prevention Of Microvascular Complications Inmentioning
confidence: 99%